Akibat Hukum Sumpah Li’an yang Tidak Terbukti Kebenarannya Terhadap Status Anak Berdasarkan Hukum Islam dan Perundang-Undangan - Hazar Kusmayanti (State Islamic University (UIN) of Sunan Ampel, 2020)
The journey of living in a household does not always go as it should. If the household has a condition that is no longer aligned, then there is most likely a dispute that leads to divorce. Often divorce occurs because the father doubts his son,or because his wife commits adultery. When this happens, the husband can swear li'an which results in breaking the marriage and the relationship with his son. This study intends to examine the legal consequences of a child in the event of divorce due to li'an oath when the allegations of adultery are not proven to be true. This Research method uses normative juridical. The results showed that if it turns out that the swearing statement uttered by the husband is not proven to be true, then the divorce becomes void. Li'an's divorce was decent by his father's son as a result of li'an's divorce. The son is returned to his father, so that he again raises the rights and obligations between the child and the father.